UNCLOS and ocean dispute settlement law and politics in the South China sea - Hong, Nong (Routledge, 2012)
"The adoption of United Nations Convention on the Law of the Sea (UNCLOS) in 1982 has led to a period of relative stability in the law of the sea. The Convention offers a legal framework for the sustainable development of the oceans and its natural resources. However, especially in recent times there have been calls to amend the Convention due to some ambiguous provisions which are unable to address many contemporary maritime issues. This book project evaluates the applicability and effectiveness of UNCLOS as a settlement mechanism for addressing ocean disputes. Focus is placed on the South China Sea (SCS) dispute, one of the most complex and challenging ocean-related conflicts in the world. The book examines how the emphasis on sovereignty, contention on energy, significance of the geographic location, threat to maritime security, overlapping maritime claims caused by the new established maritime regimes authorized by UNCLOS are all sources of the SCS dispute. The book considers the internal coherence of the Law of the Sea Convention regime and its dispute settlement procedures. It looks at the participation in the UNCLOS negotiation, maritime legislation, and dispute settlement practice of relevant States party to the dispute. The book goes on to explore the relationship between UNCLOS and other regimes and institutions in general in the SCS, particularly in regard to maritime security, marine environment protection, oil and gas joint development and political interaction. Nong Hong suggests practical mechanisms to solve the dispute and offers conclusions on the effectiveness of UNCLOS for settling disputes".